(x = 1–5): a unique series of organic superalkali cations. (16th February 2020) - Srivastava, Ambrish Kumar
Abstract : Superalkalis, having lower ionisation energy (electron affinity) than alkali atom (cation), form a very important class of clusters with several applications. With an aim to enrich the superalkali series, we have studied C x H 4 x + 1 + clusters ( x = 1–5) at dispersion-corrected density functional ωB97xD/6-311++G(d, p) level of calculations and the quantum theory of atoms in molecules (QTAIM). We notice that these C x H 4 x + 1 + cations appear as ( x - 1 ) C H 4 –CH 5 + complexes, which are stabilised by some weak and electrostatic H-bonds. Furthermore, their stability increases with the increase in x, due to the presence of dihydrogen bonds. Moreover, C x H 4 x + 1 + clusters belong to a unique series of purely hydrocarbon based organic superalkali cations as their vertical electron affinities range 4.35–2.96 eV for x = 1–5, which is in accordance with the increase in their stability. Nevertheless, the deprotonation energy and free-energy of deprotonation of C x H 4 x + 1 + clusters not only suggest their stability but also provide a suitable path of their synthesis by protonation of CH4 clusters at least in the gas phase. We believe that this unique series of non-metallic organic superalkalis will get further attention of the researchers worldwide as well as their possible applications will be explored. GRAPHICAL ABSTRACT: